A sodium aluminum lithium carbon multi-element alloy and its preparation method and application
By using sodium aluminum lithium carbon diversified alloy as a pre -sodium material, the problem of sodium loss during the first charge and discharge of sodium ion batteries, improved the energy density and cycle life of the battery, and reduced processing costs.
Patent Information
- Application Number
- CN202410464675.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-17
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-04-17
AI Technical Summary
The sodium ion battery has a large amount of sodium loss during the first charge and discharge, resulting in a significant reduction in the capacity of the entire battery, and the failure to fully utilize the performance of the positive electrode material, resulting in a reduction in the energy density of the battery.
The sodium-aluminum-lithium-carbon multi-component alloy is used as the pre-sodiumized material. It is heated and melted in an inert atmosphere to form a mixed liquid metal. The carbon material is added and stirred to form a mixed powder material, which is ground into a powder material and used as anode material for sodium-ion batteries.
It improves the energy density and cycle life of sodium-ion batteries, provides higher active sodium ions, reduces the decomposition of electrolyte under high voltage, improves material utilization, and reduces battery processing and preparation costs.
Smart Images

Figure CN118497578B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium ion battery materials, and in particular to a sodium-aluminum-lithium-carbon multi-element alloy and a preparation method and application thereof. Background Art
[0002] With the continuous growth of energy demand and the pursuit of renewable energy, high-performance energy storage technology has become the focus of today's society. Although traditional lithium-ion batteries have been widely used, their scarcity, high price and safety issues have limited their further development. Therefore, finding energy storage technologies to replace lithium-ion batteries has become a research focus for scientists. As one of the abundant elements in the earth's crust, sodium is more extensive and economically feasible than lithium. Therefore, sodium-ion batteries have received widespread attention as a new type of rechargeable battery technology. Sodium-ion batteries have better cycle stability and lower cost than lithium-ion batteries, so they are considered to be one of the energy storage solutions of the future. However, sodium-ion batteries mostly use porous carbon materials as negative electrodes, which have a large amount of sodium loss during the first charge and discharge, which significantly reduces the capacity of the entire battery, and cannot fully exert the performance of the positive electrode material, resulting in a decrease in the battery energy density.
[0003] In order to solve the above problems, pre-sodiumization technology came into being. Pre-sodiumization refers to embedding sodium ions into electrode materials through a specific treatment method before activating the sodium-ion battery for use. By pre-embedding sodium ions, the electrode material can better perform during use, replenish the active sodium loss during the first and cycle processes, and thus improve the energy density and cycle life of the sodium-ion battery.
[0004] The research and application of pre-sodiumization technology is crucial to the development of sodium-ion batteries. Scientists are constantly exploring new pre-sodiumization methods and materials to improve the performance and reliability of sodium-ion batteries. For example, some researchers are developing sacrificial materials with ultra-high capacity and environmental stability to achieve better pre-sodiumization effects. High-specific-capacity materials such as sodium oxalate, sodium citrate, sodium nitride, and sodium sulfide can be used for pre-sodiumization of sodium-ion batteries. However, these materials often have higher decomposition voltages and lower electronic conductivity. In addition, these materials often do not decompose completely, which will introduce some potential risks in the full battery system, making them often fail to achieve the expected results during actual use. In addition, the direct introduction of metallic sodium into the full battery can also greatly improve the battery capacity. However, such methods often have problems such as poor environmental stability and high processing costs, and cannot be used in large-scale production. Summary of the invention
[0005] The present invention provides a new hybrid alloy pre-sodiation material: sodium-aluminum-lithium-carbon multi-element alloy, and provides a corresponding processing and usage process, which can endow the material with both high capacity and environmental stability, provide an important method for the practical application of pre-sodiation, lay a solid foundation for the commercial application of sodium-ion batteries, and thus is expected to promote the development of the clean energy storage field. It aims to solve the problems of poor performance, reliability, environmental stability and high processing cost of existing sodium-ion batteries.
[0006] The technical solution adopted by the present invention is as follows:
[0007] A sodium-aluminum-lithium-carbon multi-element alloy, the chemical formula of the sodium-aluminum-lithium-carbon multi-element alloy is Na x Al y Li z @C, where 0.5 < x < 0.9; 0.05 < y < 0.1; 0.025 < z < 0.05. The preparation process is as follows: Under an inert atmosphere, metallic sodium and metallic aluminum are heated and melted to form a mixed liquid metal, and then metallic aluminum is dissolved in the mixed liquid metal to form a ternary liquid alloy liquid. Then, a carbon material is added to the ternary liquid alloy liquid and stirred to form a mixed powder material. After stopping heating and cooling to room temperature, a sodium-aluminum-lithium-carbon multi-element alloy is obtained, and it is ground into a sodium-aluminum-lithium-carbon multi-element alloy powder material under an inert atmosphere.
[0008] The preparation method of the sodium-aluminum-lithium-carbon multi-element alloy includes the following steps:
[0009] (1) Weigh metallic sodium, metallic aluminum and metallic lithium respectively according to the stoichiometric ratio under an inert atmosphere;
[0010] (2) Place the required metallic sodium and metallic lithium in a crucible and heat and melt them into a mixed liquid metal, and the heating temperature is 100 - 450 °C;
[0011] (3) Slowly add metallic aluminum to the mixed liquid metal obtained in step (2), and slowly stir until metallic aluminum is completely dissolved in the mixed liquid metal to form a ternary liquid alloy liquid;
[0012] (4) Slowly add the carbon material to the ternary liquid alloy liquid obtained in step (3), and slowly stir until a mixed powder material is formed;
[0013] (5) After stopping heating and waiting for the mixed powder material obtained in step (4) to cool to room temperature, grind it into a sodium-aluminum-lithium-carbon multi-element alloy powder material under an inert atmosphere.
[0014] Further, the inert atmosphere in step (1) is a helium and / or argon atmosphere.
[0015] Further, the crucible in step (2) is a metal crucible.
[0016] Furthermore, the carbon material in step (4) is one or more of conductive carbon, SP, graphite, hard carbon, and porous carbon.
[0017] Furthermore, the carbon material in step (4) is hard carbon and SP in a mass ratio of 9:1, and the total carbon mass is twice the mass of the mixed metal.
[0018] Furthermore, the powder particle size of the sodium aluminum lithium carbon multi-element alloy powder material in step (5) is less than 20 um.
[0019] The sodium-aluminum-lithium-carbon multi-element alloy is used as a sodium ion battery material.
[0020] A sodium ion battery is prepared using the sodium-aluminum-lithium-carbon multi-element alloy.
[0021] More preferably, the preparation process of the sodium ion battery is:
[0022] a. Add the adhesive to the solvent under an inert environment and heat to 45-60°C, stirring to form a colloid with a solid content of 5%;
[0023] b. Grind the sodium aluminum lithium carbon multi-element alloy into powder, and stir evenly with the resulting colloid to form a slurry;
[0024] c. The slurry obtained in step b is evenly coated on the surface of the negative electrode sheet of the sodium ion battery to obtain a negative electrode of the battery;
[0025] d. Weigh composite sodium iron pyrophosphate, PVDF, and SP in a mass ratio of 8:1:1 into an agate mortar, stir evenly, and then add an appropriate amount of NMP to prepare a slurry;
[0026] e. The slurry obtained in step d is evenly coated on a 20um aluminum foil and baked in vacuum at 80°C to form a composite sodium iron pyrophosphate positive electrode;
[0027] f. Assemble the battery negative electrode obtained in step c and the composite sodium iron pyrophosphate positive electrode sheet obtained in step e to obtain a sodium ion battery.
[0028] In summary, compared with the prior art, the present invention has the following advantages and beneficial effects:
[0029] 1. Compared with traditional sacrificial additives, the sodium-aluminum-lithium-carbon multi-element alloy provided by the present invention can provide higher active sodium ions for use in sodium ion batteries; and highly active sodium ions can be activated at a lower potential, reducing the decomposition of the electrolyte under high voltage and improving the utilization rate of the material. In addition, the sodium-aluminum-lithium-carbon multi-element alloy material itself has better electrical conductivity and is more likely to gain or lose electrons, greatly improving the utilization rate of the material itself.
[0030] 2. For the prepared battery, compared with other highly active sodium pre-sodium materials, the introduction of the adhesive organic layer (such as PEO) of the present invention can greatly improve the stability of the material or electrode in a dry aerobic environment, ensuring that the activity of the active substance will not be lost during the battery preparation process. In addition, the stability in a dry environment greatly reduces the battery processing and preparation cost, can achieve maximum utilization of materials, and has good economic value.
[0031] 3. The sodium-aluminum-lithium-carbon multi-element alloy prepared by the present invention is simple in preparation method and adopts low-temperature metallurgy, which can reduce energy consumption and enhance the commercial value of such materials. The main elements selected by the material are cheap, have high economic value, and are suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 The first charge and discharge curve of the sodium aluminum lithium carbon multi-element alloy material prepared in Example 1;
[0033] Figure 2 The first charge and discharge curves of the sodium aluminum lithium carbon multi-element alloy and hard carbon composite electrode prepared in Example 2, and the materials of Example 3 and Comparative Example 1;
[0034] Figure 3 This is a graph showing the first charge and discharge curves of the composite sodium iron pyrophosphate / sodium aluminum lithium carbon multi-element alloy and hard carbon composite electrode full battery prepared in Example 2 and the original full battery in Comparative Example 2.
[0035] Figure 4 Comparative Example 2 is used to prepare a full battery and Comparative Example 2 is used to prepare a full battery cycle graph. DETAILED DESCRIPTION
[0036] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with various embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention, that is, the embodiments described are only part of the embodiments of the present invention, rather than all of the embodiments.
[0037] The word "embodiment" used here as an "exemplary" does not necessarily mean that any embodiment described is superior to or better than other embodiments. Unless otherwise specified, the performance index tests in the embodiments of this method adopt conventional test methods in the art. The terms described in the present invention are only for describing specific implementation methods and are not intended to limit the content disclosed in the present invention.
[0038] Unless otherwise specified, the technical and scientific terms used herein have the same meanings as commonly understood by ordinary technicians in the technical field to which the invention belongs; other raw materials, reagents, experimental methods and technical means not specifically specified in the present invention refer to the raw materials and reagents commonly used by ordinary technicians in the field, as well as the commonly used experimental methods and technical means.
[0039] Example 1
[0040] This embodiment discloses a method for preparing a sodium-aluminum-lithium-carbon multi-element alloy as a pre-sodiumization material for a sodium ion battery, comprising the following steps:
[0041] S1. In a glove box filled with argon, weigh 5 g of sodium metal block, 0.14 g of lithium metal sheet, and 0.5 g of aluminum metal foil respectively;
[0042] S2. Place the required sodium metal and lithium metal in a stainless steel crucible and heat to 250° C. Stir and melt to form a mixed liquid metal. The stirring rate is 20 rpm and the liquid metal stirring time is 1 h.
[0043] S3, slowly adding the required metal aluminum to the above mixed liquid metal, and slowly stirring at about 250° C. at a stirring speed of 20-60 rpm for 2 hours until the required metal aluminum is completely dissolved to form a ternary liquid alloy;
[0044] S4, weigh 9g of hard carbon and 1g of SP for later use, slowly add the carbon material into the above ternary liquid metal, and stir continuously at about 250°C and at a stirring speed of 20rpm to form a mixed powder material;
[0045] S5. Stop heating the powder material, and after cooling to room temperature, transfer it to a pulverizer, crush it at a rotation speed of 10,000 rpm for 5 minutes, and filter the crushed powder with a sieve to form a sodium aluminum lithium carbon multi-element alloy powder material with a particle size of less than 20 um.
[0046] like Figure 1 As shown, from the first charging curve of the sodium-aluminum-lithium-carbon multi-element alloy material prepared in Example 1, it can be seen that the material can provide a capacity contribution of more than 500 mAh / g, which is much larger than conventional sodium storage materials, and can provide excess active sodium ions to supplement the capacity loss of the entire battery.
[0047] Example 2
[0048] This embodiment discloses a method for preparing a sodium ion battery using a sodium ion battery pre-sodiumization material sodium aluminum lithium carbon multi-element alloy, comprising the following steps:
[0049] S1. Weigh 5g PEO as a binder and 95ml DMC as a solvent. Pour DMC into a conical flask and add a stirrer. Heat and stir to 60°C. Slowly add PEO and stir for 2h to form a transparent colloid.
[0050] S2. In a glove box, weigh 23 g of the prepared PEO colloid into a round-bottom flask, add 10 g of the sodium aluminum lithium carbon multi-element alloy powder material prepared in Example 1, and stir at 45° C. and 20 rpm for 2 h to form a black slurry for later use;
[0051] S3, coating the above slurry on the surface of the hard carbon negative electrode, wherein the solid content in the slurry accounts for 10-15% of the hard carbon content in the hard carbon electrode, drying in a vacuum oven at 45°C for 2 hours, and rolling by a roller machine after drying to form a hard carbon negative electrode containing a sodium aluminum lithium carbon multi-element alloy;
[0052] S4, weigh 0.8g composite sodium iron pyrophosphate, 0.1g PVDF, and 0.1g SP respectively into an agate mortar, stir evenly, and then add appropriate amount of NMP to prepare a slurry;
[0053] S5, coating the slurry evenly on a 20 μm aluminum foil, and baking in vacuum at 80° C. to form a composite sodium iron pyrophosphate positive electrode;
[0054] S6. Perform a capacity test on the negative electrode sheet and assemble it with the composite sodium iron pyrophosphate positive electrode sheet into a full battery.
[0055] Example 3
[0056] This embodiment discloses a method for preparing a sodium-aluminum-lithium-carbon multi-element alloy as a pre-sodiumization material for a sodium ion battery, comprising the following steps:
[0057] S1. In a glove box filled with argon, weigh 5 g of sodium metal block, 0.14 g of lithium metal sheet, and 0.3 g of aluminum metal foil respectively;
[0058] S2. Place the required sodium metal and lithium metal in a stainless steel crucible and heat to 250° C. Stir and melt to form a mixed liquid metal. The stirring rate is 20 rpm and the liquid metal stirring time is 1 h.
[0059] S3, slowly adding the required metal aluminum to the above mixed liquid metal, and slowly stirring at 250° C. at a stirring speed of 20-60 rpm for 2 hours until the required metal aluminum is completely dissolved to form a ternary liquid alloy;
[0060] S4, weigh 9g of hard carbon and 1g of SP for later use, slowly add the carbon material into the above ternary liquid metal, and stir continuously at 250°C at a stirring speed of 20rpm to form a mixed powder material;
[0061] S5. Stop heating the powder material, and after cooling to room temperature, transfer it to a pulverizer, crush it at a rotation speed of 10,000 rpm for 5 minutes, and filter the crushed powder with a sieve to form a sodium aluminum lithium carbon multi-element alloy powder material with a particle size of less than 20 um.
[0062] from Figure 2 It can be seen that the powder formed by HC and sodium aluminum lithium alloy has the highest capacity, and the first efficiency of the battery is the highest, reaching 114%.
[0063] Example 4
[0064] This embodiment discloses a method for preparing a sodium-aluminum-lithium-carbon multi-element alloy as a pre-sodiumization material for a sodium ion battery, comprising the following steps:
[0065] Prepare the corresponding ternary liquid alloy according to S1-S3 in Example 1;
[0066] S4, weigh 8g of hard carbon and 2g of SP for later use, slowly add the carbon material into the above ternary liquid metal, and stir continuously at 250°C at a stirring speed of 20rpm to form a mixed powder material;
[0067] The remaining steps are carried out according to S5 in Example 1 to prepare a sodium aluminum lithium carbon multi-element alloy powder material.
[0068] Example 5
[0069] This embodiment discloses a method for preparing a sodium-aluminum-lithium-carbon multi-element alloy as a pre-sodiumization material for a sodium ion battery, comprising the following steps:
[0070] Prepare the corresponding ternary liquid alloy according to S1-S3 in Example 1;
[0071] S4, weigh 10 g of hard carbon for later use, slowly add the carbon material into the above ternary liquid metal, and stir continuously at 250° C. at a stirring speed of 20 rpm to form a mixed powder material;
[0072] The remaining steps are carried out according to S5 in Example 1 to prepare a sodium aluminum lithium carbon multi-element alloy powder material.
[0073] Comparative Example 1
[0074] Compared with Example 2, in which the sodium-aluminum-lithium-carbon multi-element alloy material is prepared using Example 1, this comparative example uses hard carbon and SP with a mass ratio of 9:1 as a control group to assemble a battery. The battery preparation process is as follows:
[0075] S1. Weigh 0.9g hard carbon, 0.1g PEO, and 0.1g SP into an agate mortar, stir evenly, then add appropriate amount of DMC, heat and stir to prepare a slurry;
[0076] S2, the slurry is evenly coated on a 20 μm aluminum foil, and vacuum baked at 80° C. to form an original hard carbon negative electrode;
[0077] The above electrodes were subjected to capacity tests.
[0078] like Figure 2 As shown in the first charge and discharge curves of the sodium aluminum lithium carbon multi-element alloy and hard carbon composite electrode prepared in Example 2, it can be seen that compared with the original hard carbon negative electrode (Comparative Example 1), the first charge and discharge efficiency of the battery is greatly improved, from the original 83% to 113-114%, with very excellent performance.
[0079] As shown in Table 1, when the ratio of hard carbon to SP is controlled at 9:1, the material has the best performance. Too much hard carbon will lead to poor conductivity, while too little hard carbon will increase the activity of the material but reduce its stability.
[0080] Table 1 Performance comparison of materials prepared by different schemes
[0081] Case Name First charge capacity (mAh / g) Charging capacity after 48h (mAh / g) Example 1 525 500 Example 3 551 446 Example 4 453 430 Example 5 600 378 Comparative Example 1 30 30
[0082] Comparative Example 2
[0083] Compared with the sodium aluminum lithium carbon multi-element alloy material full battery prepared in Example 2, this comparative example uses a composite sodium iron pyrophosphate positive electrode and an original hard carbon full battery as a control group, and the battery preparation process is as follows:
[0084] S1. Weigh 0.8 g composite sodium iron pyrophosphate, 0.1 g PVDF, and 0.1 g SP into an agate mortar, stir evenly, and then add appropriate amount of NMP to prepare a slurry;
[0085] S2, the slurry is evenly coated on a 20um aluminum foil, and vacuum baked at 80°C to form a composite sodium iron pyrophosphate positive electrode;
[0086] According to step S6 in Example 2, the composite sodium iron pyrophosphate positive electrode prepared in this comparative example is matched with the original hard carbon negative electrode, and the remaining steps are completed to prepare a full battery.
[0087] from Figure 3 It can be found that compared with the original composite sodium iron phosphate / hard carbon full battery, after adding the sodium aluminum lithium carbon alloy powder provided by the present invention for pre-sodiumization, the capacity of the full battery prepared in Example 2 is increased from the original 72mAh / g to 95mAh / g. Figure 4 It can be seen that the pre-sodiumization of the sodium-aluminum-lithium-carbon alloy powder provided by the present invention can greatly improve the capacity and cycle stability of the battery. The cycle life of the battery is increased from the original 80 cycle capacity retention rate of 70% to 90%, and the effect is very significant.
[0088] The above-mentioned embodiments only express the specific implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the protection scope of the present application. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the technical solution concept of the present application, and these all belong to the protection scope of the present application.
Claims
1. A sodium-aluminum-lithium-carbon multinary alloy, characterized in that: The sodium-aluminum-lithium-carbon multi-element alloy is used to prepare the negative electrode of a sodium-ion battery. The chemical formula of the sodium-aluminum-lithium-carbon multi-element alloy is Na x Al y Li z @C, where 0.5 < x < 0.9; 0.05 < y < 0.1; 0.025 < z < 0.
05. The preparation process of the sodium-aluminum-lithium-carbon multi-element alloy is as follows: Under an inert atmosphere, metallic sodium and metallic lithium are heated and melted to form a mixed liquid metal, and then metallic aluminum is dissolved in the mixed liquid metal to form a ternary liquid alloy. Next, a carbon material composed of hard carbon and SP with a mass ratio of 9:1 is added to the ternary liquid alloy. The total carbon mass of the carbon material is twice the mass of the mixed metal. Stir to form a mixed powder material, stop heating and cool to room temperature to obtain the sodium-aluminum-lithium-carbon multi-element alloy.
2. The method for preparing a sodium aluminum lithium carbon multinary alloy according to claim 1, characterized in that: The steps include: (1) Under an inert atmosphere, weigh metallic sodium, metallic aluminum, and metallic lithium respectively according to a stoichiometric ratio; (2) placing the required metallic sodium and metallic lithium in a crucible and heating and melting them into a mixed liquid metal, wherein the heating temperature is 100 to 450° C.; (3) slowly adding metallic aluminum to the mixed liquid metal obtained in step (2), and slowly stirring until the metallic aluminum is completely dissolved in the mixed liquid metal to form a ternary liquid alloy liquid; (4) slowly adding the carbon material into the ternary liquid alloy obtained in step (3), and slowly stirring until a mixed powder material is formed; (5) Stop heating and grind the mixed powder material obtained in step (4) into a sodium aluminum lithium carbon multi-element alloy powder material under an inert atmosphere after the mixed powder material cools to room temperature.
3. The method for preparing a sodium aluminum lithium carbon multinary alloy according to claim 2, characterized in that: The inert atmosphere in step (1) is helium and / or argon atmosphere.
4. The method for preparing a sodium aluminum lithium carbon multinary alloy according to claim 2, characterized in that: The crucible in step (2) is a metal crucible.
5. The method for preparing a sodium aluminum lithium carbon multinary alloy according to claim 2, characterized in that: The powder particle size of the sodium aluminum lithium carbon multi-element alloy powder material in step (5) is less than 20 μm.
6. A sodium ion battery prepared using the sodium-aluminum-lithium-carbon multi-element alloy as claimed in claim 1.
7. The sodium ion battery according to claim 6, characterized in that The preparation process of the sodium ion battery is as follows: a. Add the adhesive to the solvent under an inert environment and heat to 45-60°C, stirring to form a colloid with a solid content of 5%; b. Grind the sodium aluminum lithium carbon multi-element alloy into powder, and stir evenly with the resulting colloid to form a slurry; c. The slurry obtained in step b is evenly coated on the surface of the negative electrode sheet of the sodium ion battery to obtain a negative electrode of the battery; d. Weigh composite sodium iron pyrophosphate, PVDF, and SP in a mass ratio of 8:1:1 into an agate mortar, stir evenly, and then add an appropriate amount of NMP to prepare a slurry; e. The slurry obtained in step d is evenly coated on a 20 μm aluminum foil and baked in vacuum at 80°C to form a composite sodium iron pyrophosphate positive electrode; f. Assemble the battery negative electrode obtained in step c and the composite sodium iron pyrophosphate positive electrode sheet obtained in step e to obtain a sodium ion battery.
Citation Information
Patent Citations
Lithium-carbon-based composite negative electrode preparation method and solid-state battery
CN114284473A
Low-temperature high-voltage sodium-ion battery electrolyte and sodium-ion battery
CN117352851A